Clinical theory development: a Delphi study of influential factors - West, Darwin R. (Kansas State University, 2007)
This study made use of a three round Delphi survey process to explore the influential factors in the personal clinical theory development of marriage and family therapists. The sample consisted of marriage and family therapy trainees in COAMFTE accredited masters programs around the country. The initial round began with 64 items and resulted in 94 items. The last round resulted in 94 items being rated as to their amount of influence upon the personal clinical theory development of the trainees. A core set of variables were identified that were seen to be highly influential in the theory development process. Panelists were able to reach a strong consensus on all but one of these variables. A much larger set of variables were deemed moderately high in importance and varied in the overall degree of consensus that was obtained among all panelists. The results of this study, in terms of personal clinical theory development, point to the power of the personal relationships formed in the training process. Multiple variables related to the power of personal relationships with MFT program supervisors/professors. Key graduate and undergraduate courses were identified as being highly influential. Recommendations for future study, and program emphasis are offered.
Keywords: Marriage and Family Therapy; Clinical theory development; Education, Social Sciences (0534); Psychology, Clinical (0622)